COST ESCALATION IN THE BUILDING INDUSTRY: IMPLICATION FOR EFFICIENT PROJECT DELIVERY - Okechukwu, Onwuka (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2023)
Efficient project delivery is ubiquitous in the construction ecosystem. There is a growing concern about the effect of cost escalation in completing building projects in Nigeria. The current study assessed cost escalation in the building industry and the possible implication in project delivery. Ninety-eight professional engineers conveniently selected from building sites and other related venues completed a self-report instrument to ascertain the effect of cost escalation on a building project. The percentage scores of the data revealed that cost escalation contributes a large percentage of the delay in building projects (40.9%). The analysis also indicated that cost escalation contributes to the reduction in most building scope (33.4%) and accounts for the minimal implication relating to building project termination (24.5%).